Ciudad de Iquitos - (:unkn) unknown (My University, 1920)
Map of the city of Iquitos of the Provincial Municipality of Maynas, it shows the different public and private works carried out by this jurisdiction.

Mapa de la ciudad de Iquitos de la Municipalidad Provincial de Maynas, en ella se muestra las diferentes obras publicas y privadas realizadas por esa jurisdicción
City of Iquitos
Keywords: Incluye: Iquitos; rio Amazonas; Municipalidad provincial de Maynas; Loreto; Iquitos (Peru)--maps; Peru--cartographic materials; Peru--maps